Structure, evidence, and heuristic : evolutionary biology, economics, and the philosophy of their relationship - Schulz, Armin W. (New York, NY : Routledge, 2020)
This book is the first systematic treatment of the philosophy of science underlying evolutionary economics. It does not advocate an evolutionary approach towards economics, but rather assesses the epistemic value of appealing to evolutionary biology in economics more generally. The author divides work in evolutionary economics into three distinct, albeit related, forms: a structural form, an evidential form, and a heuristic form. He then analyzes five examples of work in evolutionary economics falling under these three forms. For the structural form, he examines the parallelism between natural selection and economic decision making, and the parallelism between natural selection and market competition. For the evidential form, he looks at the relationship between animal and human economic decision making, and the evolutionary explanation of diversity in human economic decision making. Finally, for the heuristic form, he focuses on the plausibility of equilibrium modeling in evolutionary ecology and economics. In this way, he shows that linking evolutionary biology and economics can make for a powerful methodological tool that can enable progress in our understanding of various economics questions. Structure, Evidence, and Heuristic will be of interest to scholars and advanced students working in philosophy of science, philosophy of social science, evolutionary biology, and economics.
Introduction Chapter 1: Three Forms of Evolutionary Economics Chapter 2: Economic Choice as a Selective Process (The Structural Project I) Chapter 3: Market Competition as a Selective Process (The Structural Project II)Chapter 4: Of Macaques and Men: The Comparative Approach towards Economic Decision Making (The Evidential Project I)Chapter 5: Not All the Same: The Selection-Based Approach towards Economic Chapter 6: Equilibrium Modeling: Economics, Ecology, and Evolution (The Heuristic Project) Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Evolutionary economics